Knocked silly - OAG; EMI (Malaysia). (Kuala Lumpur : EMI (Malaysia), 1999)
Contains three tracks taken from the album Melody Mocker.
CD 1 : Knocked Silly / (3:53) -- Noksili / (4:22) -- E.Q. / (3:53).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Alternative rock music; Rock music